Promoting Dealmaking? Utilitarian Religiosity and Faith Among African Neo-Pentecostal Prophets - Collium Banda (Religions, 2025)
This systematic theological study critiques the utilitarian religiosity among neo-Pentecostal prophets (NPPs) for promoting a dealmaking or ‘spiritual hustling’ approach to faith, rather than fostering a personal relationship with God. Utilitarian religiosity refers to the use of spirituality as an instrument to extract material blessings from God. NPPs represent a contemporary form of African Pentecostalism, characterised by prophetic figures who claim unique divine mandates to liberate individuals from the evil spirits believed to hinder prosperity in this life. The primary question answered in the article is as follows: how does the relational nature of faith in God in Christian theology challenge the utilitarian view of spirituality among neo-Pentecostal prophets (NPPs) in Zimbabwe? The secondary question is as follows: how should Christian faith be understood and articulated to challenge NPPs to move from utilitarian spirituality to relational spirituality? Utilitarian religiosity is critiqued for promoting a works-based relationship with God, which violates the biblical teaching that faith alone is sufficient to establish a connection with God. The NPPs’ utilitarian spirituality is critiqued from a Reformed theological emphasis on salvation by faith and challenges them to propagate a relational spirituality that comforts and empowers the poor, rather than a utilitarian spirituality rooted in dealmaking that renders God distant from those who most urgently need his presence amid existential struggles.